Hydrogen from empty cotton boll agro-waste via thermochemical route and feasibility study of operating an IC engine in continuous mode. (25th May 2017) - Das, Prasanta; Charola, Samir; Dinda, Milan; Patel, Himanshu; Maiti, Subarna
Abstract: Hydrogen can be cited as prospective source of clean power. In this work hydrogen rich syn-gas generated from the agro-waste, empty cotton bolls was injected into an IC engine in continuous mode along with gasoline. At the air-fuel ratio of 23.40, specific fuel consumption of 0.35 kg kWh −1, the engine could be operated with higher efficiency than with gasoline alone. A distinct reduction in emission characteristics could also be seen. Empty cotton bolls derived after removal of cotton from the flower in field, was first studied for fuel properties. The reasonably high heating value (HHV) of 17.54 MJ kg −1 suggested that it could be a precursor to hydrogen via two stepped thermo-chemical process. The first step involved slow pyrolysis of the biomass at 500 °C for 60 min at a heating rate of 10 °C min −1 yielding 39.71% bio-char by weight. The C, H, N, S and O contents of the produced bio-char was 59.91, 2.91, 0.72, 0.47 and 35.99% respectively and its HHV was 26.7 MJ kg −1 . Steam gasification of this bio-char, at 700 °C and water flowrate of 7 mL min −1 exhibited maximum hydrogen yield of 67.42% (v/v) in the syn-gas mixture. Subsequent enrichment of the gas using ethanolamine/ethylene diamine and KMnO4 solutions resulted in more than 90% (v/v) hydrogen in the combustible gas mixture and the test engine could be effectively operated. Graphical abstract: Highlights: Empty cotton bolls agro-waste was chosen as solid fuel for hydrogen generation. Slow pyrolysis at 500 °C yielded 39.71% bio-char. Steam gasification at 700 °C and water flowrate of 7 mL min −1 was carried out. Maximum H2 yield of 67.42% (v/v) was obtained and gas mixture was enriched. H2 rich syn-gas was run in IC engine in continuous mode along with gasoline.